The digestion time for salmon louse (Lepeoptheirus salmonis) in lumpfish (Cyclopterus lumpus) in relation to freshness, developmental stage, and temperature. - Kirstin Eliasen; Sandra Ljósá Østerø; Tróndur Tummasarson Johannesen; Esbern Jóannes Patursson; Ása Jacobsen; Agnes Mols Mortensen; Marner Nolsøe; Ása Johannesen (PLoS ONE)
Sea lice infestations cause significant economic losses in the Atlantic salmon aquaculture industry. To biologically control sea lice at farming sites, cleaner fish such as lumpfish are employed. However, the efficacy of lumpfish is under constant debate, primarily due to limited knowledge of digestion times, which makes it difficult to interpret the number of salmon lice found in the stomach contents of dissected lumpfish. The aim of this study was to provide quantitative estimates of the degradation of salmon lice over a period of 12 days. After an acclimation period of approximately one week, batches of eight lumpfish (average weight 94.3 g, SD ± 33.2) were fed salmon lice and arranged in tanks. Each batch received six large mobile lice and two adult female lice. Samplings were conducted at 24-hour intervals during the first four days and at 48-hour intervals over the remaining eight days. The experiment was conducted twice, each at a different temperature regime (6°C and 9°C), using live lice in both trials. To investigate if the freshness of the louse influenced degradation and digestion, the setup was replicated in the 9°C experiment with lice that had been stored frozen at -80°C, with an additional 12-hour sampling point for comprehensive observation. The analysis of salmon lice revealed expected digestion times of 6.4 days and 12.9 days for large mobile and adult female salmon lice, respectively. Temperature and lice freshness did not seem to influence digestion times, but the developmental stage of the lice did. The findings of this study can be used to estimate the cleaning efficacy of lumpfish based on the stomach contents.